Laboratory Assessment Revealing Nutritional Disorders Among Children in Uzbekistan - N. A. Ergasheva (Academia Open, 2025)
General Background: Childhood nutritional disorders pose major global health risks, affecting growth, immunity, and long-term metabolic outcomes. Specific Background: In Uzbekistan, a dual burden of micronutrient deficiencies and rising overweight rates persists, yet no standardized national protocol exists for laboratory-based assessment. Knowledge Gap: Existing monitoring systems lack unified biochemical, anthropometric, and dietary evaluation methods, limiting early detection and regional comparability. Aims: This study aims to develop and validate a comprehensive laboratory protocol for assessing the nutritional status of children aged 2–12 years to support early prevention of alimentary disorders. Results: Analysis of 500 children across Uzbekistan showed high prevalence of vitamin D deficiency (46 percent), iron deficiency indicated by low ferritin levels (32 percent), and early overweight or obesity (14 percent). Significant correlations were identified between micronutrient biomarkers, BMI, waist circumference, dietary patterns, and sunlight exposure, confirming the multifactorial nature of nutritional imbalance. Novelty: The study introduces the first unified framework integrating biochemical, anthropometric, and dietary indicators tailored to Uzbekistan’s pediatric population. Implications: Adoption of this standardized protocol can strengthen national monitoring, improve early diagnosis of hidden deficiencies, guide evidence-based interventions, and support long-term strategies to reduce alimentary and metabolic disorders among Uzbek children.Highlight : The content highlights the significant dual burden of micronutrient deficiencies and early obesity among children in Uzbekistan. It emphasizes the importance of integrating biochemical, anthropometric, and dietary data for accurate early detection. The study supports establishing a standardized laboratory protocol to improve preventive care and national monitoring. Keywords : Nutritional status of children, micronutrient deficiencies, vitamin D deficiency, iron deficiency anemia, childhood obesity